Aktivitas Makroalga sebagai Agen Antikanker Serviks - Yosi Dwi Saputra (SENTRI: Jurnal Riset Ilmiah, 2025)
One of the causes of death in the world is cancer. This situation is caused by the excessive development of body tissue cells that become tumors. Over the past few years, significant progress has been made in reducing cases and deaths from cervical cancer through prevention and treatment strategies. Macroalgae are marine organisms that can be used as a source of natural medicine to eradicate cancer. Active ingredients such as flavonoids, alkaloids, tannins, triterpenoids, polyphenols and steroids can act as anti-cancer agents. Genes found in macroalgae such as Bcl2 and p53 can influence the cell cycle in cancer growth. The purpose of this paper is to analyze the cytotoxic content as well as to test the phytochemical, anticancer activity and determine its potential as an anti-cancer agent which is widespread in Indonesian waters. The compilation of this bibliographic search used secondary research methods by collecting research topic data from various non-electronic and electronic libraries. The results of the review were obtained from several journals: the mechanism of antineoplastic agents against viruses and the cytotoxic activity of macroalgae against HeLa cells. Large algae have a cytotoxic action that can reject HeLa cells, so they can be used as variations in the production of cervical anticancer drugs. In the Indonesian seas, large algae grow abundantly and are used as medicinal ingredients to reduce the number of deaths from tumors.